Network analysis of stress and stigma symptoms and their associations with quality of life among Chinese female infertility patients - Fang Liu; Wenju Han; Wei Qiao; Zhihan Chen; Yingbo Chen; Ruonan Lu; Junqiao Qi; Xiuxia Yuan; Xueqin Song; Dongqing Zhang (BMC, 2024)
Abstract Background This study has employed network analysis while investigating the interrelationships among stress and stigma symptoms and their associations with quality of life among Chinese female infertility patients. Methods In this cross-sectional study, 428 female patients who visited the Department of Reproductive Center of Dalian Women and Children's Medical Group with chief complaints of infertility symptoms were recruited using convenience sampling from November 2022 to December 2023. Fertility-related stress and stigma status were examined by the Fertility Problem Inventory (FPI) and Infertility Stigma Scale (ISS), respectively. Quality of life was examined by the Fertility Quality of Life (FertiQoL). Network analysis was conducted to estimate the network of stress and stigma symptoms. The flow network approach was used to identify specific stigma and stress symptoms related to quality of life. Expected influence (EI) and bridge expected influence (bEI) were used to quantify central and bridge symptoms in the network, respectively. The bootstrapping method evaluated the accuracy and robustness of the network estimates. Results The average predictability of FPI and ISS symptoms was 0.67. The "relationship concern" was the most central symptom across all centrality indices, followed by "public stigma" and "social concern". The main symptoms bridging the FPI and ISS clusters were "self-devaluation", "social concern", and "relationship concern". The network demonstrated robustness in stability and accuracy tests. In the flow network, "social withdrawal" and "self-devaluation" showed strong negative associations with FertiQoL. Conclusions "Relationship concern," "public stigma," "social concern," and "self-devaluation" have been identified as the main central and bridge symptoms in the stress and stigma network in this study. Notably, stigma symptoms, particularly "social withdrawal" and "self-devaluation", showed stronger associations with FertiQoL compared to stress symptoms, highlighting their importance in potential treatment strategies.